Integrated metabolomics and transcriptomics analysis reveals the mechanism of Tangbi capsule for diabetic lower extremities arterial disease - Luo, Ye-hao; Wang, Da-wei; Yao, Jia; Hu, Yue; Zhao, Ling; Wen, Jian-xuan; Zhang, Jin-ming; Wu, Lu-Lu; Fan, Guan-jie; Song, Wei (Frontiers in Microbiology, 2024)
Objective: Tangbi capsule (TBC) is a traditional Chinese medicine prescription, which has the potential to improve the vascular insufficiency of lower extremities and limb numbness in diabetes.However, the potential mechanism remains unknown. This study aims to investigate the pharmacological effects and mechanism of TBC on rats with diabetic lower extremities arterial disease (LEAD).The mechanism of TBC on diabetic LEAD was investigated through metabolomics and transcriptomics analysis, and the main components of TBC were determined by mass spectrometry.The efficacy and mechanism of TBC on diabetic LEAD rats were investigated through in vitro experiments, histopathology, blood flow monitoring, western blot, and RT-PCR.Results: Mass spectrometry analysis identified 31 active chemical components in TBC including (2R)-2,3-Dihydroxypropanoic acid, catechin, citric acid, miquelianin, carminic acid, salicylic acid, formononetin, etc. In vitro analysis showed that TBC could reduce endothelial cell apoptosis and promote angiogenesis. Histopathological analysis showed that TBC led to an obvious improvement in diabetic LEAD as it improved fibrous tissue proliferation and reduced arterial wall thickening. In addition, TBC could significantly increase the expression levels of HIF-1α, eNOS, and VEGFA proteins and genes while reducing that of calpain-1 and TGF-β, suggesting that TBC can repair vascular injury. Compared with the model group, there were 47 differentially expressed genes in the whole blood of TBC groups, with 25 genes upregulated and 22 downregulated. 87 altered metabolites were identified from the serum samples. Combining the changes in differentially expressed genes and metabolites, we found that TBC could regulate arginine biosynthesis, phenylalanine metabolism, pyrimidine metabolism, arachidonic acid metabolism, pyrimidine metabolism, arachidonic acid metabolism, nucleotide metabolism, vitamin B6 metabolism and other metabolic pathways related to angiogenesis, immune-inflammatory response, and cell growth to improve diabetic LEAD.TBC improved vascular endothelial injury, apoptosis, lipid accumulation, liver and kidney function, and restored blood flow in the lower extremities of diabetic LEAD rats. The mechanism of TBC in the treatment of diabetic LEAD may be related to the modulation of inflammatory immunity, lipid metabolism, and amino acid metabolism. This study presented preliminary evidence to guide the use of TBC as a therapy option for diabetic LEAD.